2023
DOI: 10.1063/5.0156999
|View full text |Cite
|
Sign up to set email alerts
|

Constraining chaos: Enforcing dynamical invariants in the training of reservoir computers

Jason A. Platt,
Stephen G. Penny,
Timothy A. Smith
et al.

Abstract: Drawing on ergodic theory, we introduce a novel training method for machine learning based forecasting methods for chaotic dynamical systems. The training enforces dynamical invariants—such as the Lyapunov exponent spectrum and the fractal dimension—in the systems of interest, enabling longer and more stable forecasts when operating with limited data. The technique is demonstrated in detail using reservoir computing, a specific kind of recurrent neural network. Results are given for the Lorenz 1996 chaotic dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…More recently, Platt et al. (2023) showed that constraining these macro‐scale parameters using global invariant properties of the underlying system leads the optimization algorithm to select parameters that generalize well to unseen test data. In that work, the authors were successful in using the largest positive Lyapunov exponent, and to a lesser extent the fractal dimension of the system.…”
Section: Echo State Network Prediction Skillmentioning
confidence: 99%
“…More recently, Platt et al. (2023) showed that constraining these macro‐scale parameters using global invariant properties of the underlying system leads the optimization algorithm to select parameters that generalize well to unseen test data. In that work, the authors were successful in using the largest positive Lyapunov exponent, and to a lesser extent the fractal dimension of the system.…”
Section: Echo State Network Prediction Skillmentioning
confidence: 99%